Implementation of audiovisual resources through a system of classes for the development of pronunciation. - Chamba Encalada, Thalia Del Cisne; Enríquez Pacheco, Britney Pauleth (Machala: Universidad Técnica de Machala, 2024)
The objective of this research project is to implement a class system through audio-visual resources for developing English pronunciation in 8th-year students of General Basic Education at Nueve de Octubre High School. It is carried out from a quantitative methodological paradigm, with an experimental design of an explanatory-transversal type. The study variables are the classroom system through the use of audio-visual resources as an independent variable and pronunciation development as a dependent variable. The population is constituted of the students of the institution as mentioned earlier, of which 30 eighth-grade students were taken as a sample. The instruments used were observation, diagnostic tests, and evaluation. The results were processed through a frequency table, the percentage, and the chi-square to make the comparison.
El objetivo de este proyecto de investigación es implementar un sistema de clases a través de recursos audiovisuales para desarrollar la pronunciación del inglés en estudiantes de 8º año de Educación General Básica del Colegio de Bachillerato Nueve de Octubre. Se realiza desde un paradigma metodológico cuantitativo, con un diseño experimental de tipo explicativo-transversal. Las variables de estudio son el sistema de clases mediante el uso de recursos audiovisuales como variable independiente y el desarrollo de la pronunciación como variable dependiente. La población está constituida por los estudiantes de la institución como se mencionó anteriormente, de los cuales se tomó como muestra 30 estudiantes de octavo grado. Los instrumentos utilizados fueron la observación, las pruebas diagnósticas y la evaluación. Los resultados fueron procesados a través de una tabla de frecuencias, el porcentaje y el chi cuadrado para realizar la comparación.
Keywords: AUDIO-VISUAL RESOURCES; CLASS SYSTEM; PRONUNCIATION; DIAGNOSTIC TEST